A Simple Theoretical Model Explains Dynein's Response to Load - Gao, Yi Qin (Biophysical journal, 2006)
Recent experiment showed that cytoplasmic dynein 1, a molecular motor responsible for cargo transport in cells, functions as a gear in response to external load. In the presence of vanishing or small external load, dynein walks with 24- or 32-nm steps, whereas at high external load, its step size is reduced to 8nm. A simple model is proposed to account for this property of dynein. The model assumes that the chemical energy of ATP hydrolysis is used through a loose coupling between the chemical reaction and the translocation of dynein along microtubule. This loose chemomechanical coupling is represented by the loosely coupled motions of dynein along two different reaction coordinates. The first reaction coordinate is tightly coupled to the chemical reaction and describes the protein conformational changes that control the chemical processes, including ATP binding and hydrolysis, and ADP-Pi release. The second coordinate describes the translocation of dynein along microtubule, which is directly subject to the influence of the external load. The model is used to explain the experimental data on the external force dependence of the dynein step size as well as the ATP concentration dependence of the stall force. A number of predictions, such as the external force dependence of speed of translocation, ATP hydrolysis rate, and dynein step sizes, are made based on this theoretical model. This model provides a simple understanding on how a variable chemomechanical coupling ratio can be achieved and used to optimize the biological function of dynein.